Elicitation and enhancement of phenolics and flavonoids production in Clinacanthus nutans cultures / Saiyidah Nafisah Hashim - Hashim, Saiyidah Nafisah (2023)
Clinacanthus nutans (C. nutans) plant possesses with antioxidant properties that are attributed to the presence of phenolics and flavonoids compound. However, the compounds concentration in plants is sometimes quite low, varies according to development stage and limited by environmental constraints. Elicitation technique have been recommended as an efficient method of large producing plant beneficiary compounds in in vitro plant at short period of time. Thus, the aim of this study was to increase the phenolic and flavonoid content of C. nutans by eliciting the in vitro cultured plant cell and tissue. The research method started with axenic culture establishment by surface sterilization, followed by the optimization of culture medium for production of differentiated plant tissue. For callus and cell suspension, the culture medium and condition had been optimized. A comparison on bioactive compound and antioxidant activities between regenerated shoots, roots, callus and cell were done. In the elicitation step, in vitro cultured and intact plant were treated with wood vinegar (WV), methyl jasmonate (MJ), and yeast (Y). Chalcone synthase enzyme activities and quercetin quantification were measured from all treated samples.